2010
DOI: 10.1007/s00572-010-0333-3
|View full text |Cite
|
Sign up to set email alerts
|

Agroecology: the key role of arbuscular mycorrhizas in ecosystem services

Abstract: The beneficial effects of arbuscular mycorrhizal (AM) fungi on plant performance and soil health are essential for the sustainable management of agricultural ecosystems. Nevertheless, since the 'first green revolution', less attention has been given to beneficial soil microorganisms in general and to AM fungi in particular. Human society benefits from a multitude of resources and processes from natural and managed ecosystems, to which AM make a crucial contribution. These resources and processes, which are cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
411
0
22

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 788 publications
(475 citation statements)
references
References 97 publications
8
411
0
22
Order By: Relevance
“…of biotic and abiotic stresses, reducing the need of chemical fertilizers and pesticides and consequently the environmental impact of agriculture (Smith and Read 2008). Moreover, AMF provide key ecosystem services, such as soil aggregation and C sequestration (Gianinazzi et al 2010) and may stimulate the biosynthesis of beneficial plant secondary metabolites, contributing to the production of safe and high quality food . A large body of investigations showed that AMF uptake and transfer soil mineral nutrients, such as phosphorus (P), nitrogen (N), sulphur (S), potassium (K), calcium (Ca), iron (Fe), copper (Cu) and zinc (Zn) by means of extraradical mycorrhizal hyphae, which spread from colonized roots into the soil (Giovannetti et al 2001;Avio et al 2006;Blanke et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…of biotic and abiotic stresses, reducing the need of chemical fertilizers and pesticides and consequently the environmental impact of agriculture (Smith and Read 2008). Moreover, AMF provide key ecosystem services, such as soil aggregation and C sequestration (Gianinazzi et al 2010) and may stimulate the biosynthesis of beneficial plant secondary metabolites, contributing to the production of safe and high quality food . A large body of investigations showed that AMF uptake and transfer soil mineral nutrients, such as phosphorus (P), nitrogen (N), sulphur (S), potassium (K), calcium (Ca), iron (Fe), copper (Cu) and zinc (Zn) by means of extraradical mycorrhizal hyphae, which spread from colonized roots into the soil (Giovannetti et al 2001;Avio et al 2006;Blanke et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizal (AM) fungi contribute greatly to crop productivity and ecosystem sustainability in new plant production strategies (Gianinazzi et al 2010) and are essential for the sustainable management of agricultural ecosystems (Jeffries et al 2003;Smith and Read 2008;Barrios 2007). They promote the accumulation of effective ingredients of medicinal plants, which has become a hot area of research lately.…”
Section: Introductionmentioning
confidence: 99%
“…Those fungi provide several ecosystem services including promoting plant growth and nutrient uptake, increasing plant resistance to drought along with protection against biotic stresses, and enhancing soil stability and water retention (Gianinazzi et al 2010). Therefore, that symbiotic association constitutes an key strategy for assisting plants to cope with extreme environmental conditions (Smith & Read 2008), such as occur in high-altitude ecosystems.…”
Section: Introductionmentioning
confidence: 99%